Implications of precordial ST segment depression during acute inferior myocardial infarction. Arteriographic and ventriculographic correlations during the acute phase. - Cohen, M (1984)
Thirty two patients presenting with acute transmural inferior wall myocardial infarction underwent cardiac catheterisation and angiography within 12 hours of the onset symptoms. Twelve lead electrocardiograms performed within one hour of catheterisation showed ST segment depression in the anterior precordial leads in addition to inferior wall changes in 17 patients and no ST segment changes in the anterior leads in 15. When the clinical, arteriographic, and ventriculographic variables were compared between the two groups no significant differences were noted with regard to age, sex, risk factors for coronary disease, duration of symptoms before angiography, Killip class, number of inferior leads with ST segment elevation, or initial serum creatine kinase activity. The extent of coronary artery disease as well as the prevalence of severe disease in the left anterior descending artery were similar for both groups. Biplane left ventriculography showed no significant differences between the two groups with regard to global ejection fraction or to the prevalence of posterolateral or anterior segmental wall motion abnormalities.